Midwifery students' educational experiences, professional identity, and future expectations: a cross-sectional study in Eastern Turkey - Oner, Serap; Kartal, Sibel Akgul (Bmc, 2026)
Background Midwifery education involves not only the acquisition of clinical knowledge and technical skills but also the development of professional values, attitudes, and identity essential for woman-centred care. Although midwifery education in Turkey has undergone substantial reform, disparities in educational resources and clinical learning opportunities persist, particularly in Eastern regions. This study aimed to explore midwifery students' educational experiences, professional perceptions, and future expectations in Eastern Turkey. Methods A cross-sectional descriptive study was conducted between November and December 2025 among undergraduate midwifery students at two public universities in Eastern Turkey (F & imath;rat University and Van Y & uuml;z & uuml;nc & uuml; Y & imath;l University). All eligible students were invited to participate using a census sampling approach. Data were collected via an anonymous, self-administered online questionnaire covering educational experiences, professional identity and engagement, and views on professional development and future expectations. Descriptive statistics were used, and group comparisons were performed using Kruskal-Wallis, Mann-Whitney U, and chi-square tests. Statistical significance was set at p < 0.05. Results A total of 495 students participated (mean age 21.1 +/- 3.4 years). Overall satisfaction with studying midwifery was high, with 36.8% reporting satisfaction and 32.9% reporting high satisfaction. Most students perceived theoretical course hours (89.9%) and clinical practice hours (76.2%) as adequate; however, only 25.5% reported adequate laboratory and simulation facilities. Professional identity development was reported by 87.7% of participants, and 81.2% expressed a positive outlook toward their professional future. A substantial proportion of students reported a preference for working in hospital units other than the labour ward after graduation. Satisfaction did not differ by year of study (Kruskal-Wallis H = 2.68, p = 0.443). Perceptions of simulation adequacy differed significantly between universities (chi & sup2; = 9.43, p = 0.002). Mentor support was not associated with overall satisfaction (Mann-Whitney U = 30,882.0, p = 0.422), whereas professional identity was significantly associated with a positive professional outlook (chi & sup2; = 7.92, p = 0.005). Conclusions Midwifery students in Eastern Turkey reported generally positive educational experiences and strong professional identity development, but also identified important gaps in access to simulation-based training. Strengthening simulation capacity and systematically supporting professional identity formation are essential to improve educational equity and to ensure long-term commitment to clinical midwifery practice.
Keywords: Midwifery education; Professional identity; Simulation-based training; Mentorship; Student perceptions